Psicologia Cognitiva e Alfabetização: impacto da instrução fônica apoiada em materiais montessorianos - Furtado, Daniela Tubini (2016)
Previous studies showed that Cognitive Psychology has been contributing a lot for the development of the scientific knowledge about the initial learning of reading and writing. Many intervention programs have proved that working with metalinguistics abilities can accelerate the initial learning of writing and reading, especially when it is referred to phonological awareness and, specifically to the phonemic awareness. According to the literature, the present study verified the effects of a learning program of an alphabetic system using Montessorian materials that correspond to the characteristics of the metalinguistic approach, to impel the learning process of six-year-old children that present lower performance in reading and writing when compared to children the same age and school. The research was accomplished in a private school located in the ABC paulista area. The participants were 40 students enrolled in the Year 1 of the Elementary School, with average of 6 and a half years old. There were two groups: Intervention Group (IG), composed by 20 children who presented lower performance in the reading and writing ability in an initial assessment done in March by the teacher from Year 1; and the Comparison Group (CG), composed by 20 children that were randomly chosen among the ones with medium to above medium performance in the same assessment done in March. The data collection was composed of four moments: the initial assessment, done in March by the teachers from the regular classes; the assessment before the intervention program, done only for the IG, in June, by the researcher; the partial assessment of reading and writing, done in September by the researcher in both groups, IG and CG; and the final assessment, done in December by the researcher, also in both groups. The intervention program was composed by 30 Montessorian Literacy games, and only the children from the IG group participated in this program. The results showed positive effects of the intervention program on the development of the IG children in the writing abilities as well as the reading ones, when a comparison was made. But, when the children from both groups were compared, there was no statistically significant difference, which makes us conclude that, after the intervention, the children from IG presented a performance as good as the children from CG